Bifunctional Fe(ii) spin crossover-complexes based on ω-(1H-tetrazol-1-yl) carboxylic acids. Issue 47 (13th November 2020) - Zeni, Willi; Seifried, Marco; Knoll, Christian; Welch, Jan M.; Giester, Gerald; Stöger, Berthold; Artner, Werner; Reissner, Michael; Müller, Danny; Weinberger, Peter
Abstract : Carboxylic acid functionalized tetrazoles form Fe(ii ) spin crossover materials governed by H-bonding networks. Abstract : To increase the supramolecular cooperativity in Fe(ii ) spin crossover materials based on N1-substituted tetrazoles, a series of ω-(1 H -tetrazol-1-yl) carboxylic acids with chain-lengths of C2 –C4 were synthesized. Structural characterization confirmed the formation of a strong hydrogen-bond network, responsible for enhanced cooperativity in the materials and thus largely complete spin-state transitions for the ligands with chain lenghts of C2 and C4 . To complement the structural and magnetic investigation, electronic spectroscopy was used to investigate the spin-state transition. An initial attempt to utilize the bifunctional coordination ability of the ω-(1 H -tetrazol-1-yl) carboxylic acids for preparation of mixed-metallic 3d–4f coordination polymers resulted in a novel one-dimensional gadolinium-oxo chain system with the ω-(1 H -tetrazol-1-yl) carboxylic acid acting as μ2 -η 2 :η 1 chelating–bridging ligand.